25 Years of the Southern Skies Monitoring by OGLE: Workshop 4. Issue Volume 14:Issue S339(2018) (November 2017) - Wyrzykowski, Ł.; Pietrukowicz, P.; ,
Abstract: The Optical Gravitational Lensing Experiment (OGLE) started at Las Campanas Observatory in 1992 with a pilot monitoring programme of two million stars in the Galactic Bulge. It is still operating today, collecting time-domain photometric data of a billion stars from the densest regions in the southern sky. Among its main achievements are discoveries of thousands of microlensing events, a few dozen extrasolar planets and candidates for black holes, a million variable stars, and thousands of quasars and supernovæ. It has made a major contribution to the studies of the dark-matter content of the Milky Way halo, the structure of the Galactic Bulge, the Magellanic Clouds, and new classes of variable stars. In this its 25 th anniversary year, we presented a selection of the major scientific highlights of OGLE.